PENERAPAN SKEMA INSENTIF, TINGKAT KOMITMEN ORGANISASI DAN PENGARUHNYA TERHADAP ESCALATION OF COMMITMENT - Caesar Marga Putri (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Abstract: The aim of this research is to investigate the effect of reward and punishment in escalation of commitment. The escalation of commitment is usually attributed to the decision maker if the project is unfavorable. This research also investigates the effect of organizational commitment to the decision to escalate or not to escalate the commitment. Experimental method is used in this research. There are 37 participants contribute to this research. The result of this research shows that the escalation of commitment level is higher if there is reward and punishment provided in the organization than if only reward provided. In other hand this level is higher if only punishment provided than if reward and punishment provided. It is mean that decision makers will avoid punishment, so they escalate their commitment. As predicted before organization commitment also effect escalation of commitment.  The result shows that organizational commitment will decrease the level of escalation of commitment.Keywords: Escalation of Commitment, Organizational Commitment, Punishment, Reward.